Designing Effective Objective Structured Clinical Examinations (OSCEs) for Skill Assessment - Ayesha Tariq, Farrukh Hassan Rizvi, Shabir Ahmad, Misbah Ul Hasan Ghani, Aisha Zia Butt, Syed Shah Faisal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective structured clinical examinations (OSCEs) represent the principal performance-based assessment of clinical competence across health professions but require rigorous design to ensure validity, reliability and educational impact. The present work describes a structured framework for OSCE development and evaluation, and reports an experimental implementation in a mid-level undergraduate clinical cohort (n = 120) comparing a blueprint-driven, competency-mapped OSCE (intervention) with a conventionally assembled OSCE (control).